Radiation in Adolescent Idiopathic Scoliosis Management: Estimated Cumulative Pre-Operative, Intra-Operative, and Post-Operative Exposure - Duke A; Marchese R; Komatsu DE; Barsi J (Orthopedic Research and Reviews, 2022)
Alexander Duke, Richard Marchese, David E Komatsu, James Barsi Department of Orthopaedics and Rehabilitation, Stony Brook University Hospital, Stony Brook, NY, USACorrespondence: Alexander Duke, Stony Brook University Hospital, Health Sciences Center T18-089, Stony Brook, NY, 11794, USA, Tel +1 631 972-8324, Fax +1 631 444-3502, Email alexander.duke@stonybrookmedicine.eduBackground: Adolescent Idiopathic Scoliosis (AIS) is the most common type of scoliosis affecting adolescents, with approximately 2– 4% of children being diagnosed. Crucial to the diagnosis and management are radiographic imaging, which allow physicians to assess and treat – from initial visits through surgical planning and post-operative management. While initial stages require low levels of exposure to radiation, via x-rays, as patients progress in disease severity exposure becomes larger with pre-operative, intra-operative and post-operative CT scans. While many studies have evaluated exposure during AIS treatment, few have assessed the cumulative radiation exposure adolescents receive during their evaluation. The purpose of our study is to complete a comprehensive review on cumulative radiation exposure and determine what stages in AIS treatment expose patients to the highest level of radiation over a duration of 2 years.Methods: A retrospective chart review of 109 AIS cases (29M, 80F), mean age 14.9 ± 2.3 years was completed to assess and quantify each imaging modality used. Employing a radiation detector, each imaging modality was then assessed, and estimated radiation exposures were determined. Statistical analysis was completed utilizing averaged patient exposures during each selected period in AIS management.Results: Mean estimated radiation doses (StDev) were 60.94 mrem (± 0.609 mrem) for two x-rays (full-length AP and lateral radiograph of the entire spine), 12.92 mrem (± 1.292 mrem) for each fluoroscopy exposure, and 1340.60 mrem (± 13.406 mrem) per CT scan. Based on these values, estimated subject exposures were calculated. The total estimated radiation exposure over a 2-year period was 5572.74 mrem (± 1428.88 merm) or 2786.37 mrem (± 714.43 mrem) per year.Conclusion: The two-year cumulative radiation exposure is below the recommended exposure by Nuclear Regulatory Commission and OSHA. As expected, CT exposure presents the largest radiation exposure to patients with AIS throughout their operative management.Level of Evidence: III, retrospective study.Keywords: scoliosis, radiation, adolescent idiopathic scoliosis